PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) DI KELAS IV SDN 060857 MEDAN - Riska Meisyi Putri; Mandra Saragih; Irayanti Masta M Silalahi (STKIP Subang, 2025)
This research is motivated by the low Mathematics learning outcomes of fourth-grade students at SDN 060857 Medan who have not yet reached the Minimum Completion Criteria (KKM) of 70. Based on initial observations, students have difficulty in understanding the concept of fractions. This study aims to improve Mathematics learning outcomes through the implementation of the Indonesian Realistic Mathematics Education Approach (PMRI). The method used is Classroom Action Research (CAR) which was implemented in two cycles in the 2024/2025 Academic Year with a total of 28 students. Each cycle consists of planning, implementation, observation, and reflection stages. The results of the study indicate that the PMRI approach is effective in improving learning outcomes. In cycle I, 19 students (67%) achieved the KKM. After improvements and adjustments to learning in cycle II, the number of students achieving the KKM increased to 26 (92%). In addition, teacher activity and student involvement in the learning process also increased. Thus, the PMRI approach is proven to be able to create contextual and meaningful learning, as well as improve Mathematics learning outcomes in fractions.